BIOPLASTIC PACKAGING’S POTENTIAL AND ENERGY EFFICIENCY - Levičar, Stanislav; Lisec, Andrej (Journal of Energy Technology, 2024)
he search for alternatives to petroleum-based plastics is multi-layered and motivated by various negative aspects, such pollution, toxicity, and difficult degradability, as well as issues regarding recycling, energy consumption, CO 2 emissions, and others. Since researchers and supply chains aim to evaluate the entire lifecycle of the production of goods, a wide range of materials are usually identified as potential substitutes to petroleum-based plastics, but when considering physical characteristics, bioplastics offer the most convenient replacement options. This article is a review the current state of its usage, and attempts to identify the approach that would make the adoption of bioplastics in packaging more viable, even though they are still in the early phases of development.